Adoption of Powertrain Technologies in Automobiles-A System Dynamics Model of Technology Diffusion in the American Market - Liu, Chen; Rouse, Willian Bill; Hanawalt, Edward S. (IEEE transactions on vehicular technology, 2018)
The American automobile industry is facing substantial environmental and energy challenges driving the pursuit of alternative powertrain technologies-"The intervening mechanism by which power is transmitted from an engine to a propeller or axle that it drives," which nominally includes engine, transmission, drive shafts, differentials, and the final drive. Emerging alternative fuel vehicles are showing their potential to address these challenges. However, diffusion of new technologies has many complications. This paper uses system dynamics modeling to investigate the impacts of individual and organizational parameters. This model embeds two traditional modeling methods for technology adoption, the Bass diffusion model and multinomial logit regression method. Five types of powertrain systems and three major stakeholders are considered. Mathematical relationships among different variables are elaborated. The qualitative impacts of government feebate, manufacturer willingness, and consumer purchasing preferences on economic and environmental issues are addressed using scenario analysis.